Use of the Read, Answer, Discuss, Explain and Create Learning Model in Science Learning Knowledge Nature to Improve Elementary School Students' Ability to Understand Concepts - Nur Aulya Maulida; D. Fadly Pratama; Jajang Bayu Kelana (Journal of Education and Teacher Training Innovation, 2023)
Students' understanding of concepts is a form of ability to master a number of learning materials, where students do not just know and remember, but are able to re-express the concepts they understand using their own language or in a form that is easier to understand and comprehend. able to apply. The purpose of this research is to determine the increase in students' conceptual understanding abilities by using the RADEC learning model in science learning. The research method used is a mixed method with a sequential explanatory research design. The population in this study were all students in one of the West Bandung Regency elementary schools with a sample of 35 grade IV students. The instruments used in this research were test and non-test instruments. Data analysis techniques were carried out in a way Qualitative and quantitative . The results of this research are based on the results of pretest and posttest answers to students' concept understanding abilities. To strengthen these results, observations, interviews and distribution of student questionnaires were carried out regarding the difficulties of teachers and students in implementing this learning activity. Based on the results of data analysis, it can be concluded that the use of the RADEC learning model can improve the ability to understand concepts in class IV students as evidenced by the sig (Paired Sample T-Test) value of 0.000 < 0.05